Ensiled green tea and black tea waste as protein supplement for goats - Kondo M.; Hidaka M.; Kita K.; Yokota H. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Tea waste, a by-product from beverage companies producing a ready-made tea drink, contains substantial concentrations of crude protein (CP, 25 ~ 30% of the DM), which may have value as a dietary supplement for goats. Tea waste also contains 6.1 ~ 9.6% total extractable tannins and 0.8 ~ 2.4% condensed tannins in the DM. In vitro gas production and in vivo digestibility of green tea waste silage (GTWs) and black tea waste silage (BTWs) were compared to lucerne hay cubes (LHC). In vitro gas production from BTWs was significantly lower than LHC and GTWs. Addition of polyethylene glycol as a tannin-binding agent to BTWs, increased gas production but did not affect LHC and GTWs. In vivo digestibility, nitrogen balance and ruminal NH3-N concentration were determined using four castrated Japanese goats fed diets of timothy hay + wheat bran (control), control + LHC, control + GTWs and control + BTWs, in a 4 x 4 Latin Square Design. Timothy hay and wheat bran were offered equally in all treatments, and LHC, GTWs and BTWs were supplied on a CP basis, contributing 15.6% of the total CP intake. DM, CP and NDF digestibility were not affected by the type of supplement (p
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)